Distribution and habitat suitability of Amorphophallus gigas with MaxEnt modeling in north Sumatra, Indonesia - Rambey, Ridahati; Rahmawaty; Rauf, Abdul; Nababan, Esther Sorta Mauli; Delvian; Aththorick, T. Alief; Ismail, Mohd Hasmadi; Saputra, Muhammad Hadi; Gandaseca, Seca; Suratman, Mohd Nazip (Zoo Outreach Organisation, 2025)
Amorphophallus gigas is exclusively found in community agroforestry gardens within the northern Sumatra region, Indonesia. This species faces various threats including land conversion and tuber extraction for economic purposes. Despite its unique habitat characteristics, the conservation status remains unrecorded on the IUCN Red List. Effective conservation requires comprehensive data, including distribution and habitat conditions in the field. Therefore, this study aimed to analyze the variables affecting the distribution of A. gigas in northern Sumatra and predict the size of the area with the potential for spread. The variables examined included height, slope, slope direction, climatic conditions, and land cover. Coordinate points were taken directly in the field using GPS, while Maximum Entropy (MaxEnt) modeling was used to predict the suitability of the habitat of the species. MaxEnt modeling of variables affecting the distribution of A. gigas showed that soil type played an important role (contribution 55%), followed by the average monthly temperature range (16%), and altitude (7.9%). The most suitable area was found to be located in the southern part of the province. The results of this research are useful for formulating conservation strategies for A. gigas.